(3eSfO GdEeGe CHj MfjaI GdfYeGfs - (3CHh MfjaI , CHh MfjaI,J (B150 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdMGaX CHh fYje CMeO Hf YHO Gddg Hf CMeO Hf ESMb GdCUHgGfi PcQ eG GfJgi EdjfG ef eSGfjO MOjK GdEeGe CHj MfjaI GdfYeGf Hf KGHJ Gdchai s
(3BNQgG (B:s
(3QhGjJg Yf CHj CejI hgh YHO GdcQje GdNhQi hef JbOeg BNQg hGdMeO ddg Mb MeOg s
(3Ydjg SeGY SfI (B540 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B36 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B104s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1680s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(265) s
Keywords: (3GdMOjK h GdeUWdMs